Biomass and biofuels - Fiala Marco; Nonini Luca (EPJ Web of Conferences, 2018)
Biomass includes all materials that contain organic carbon bound in the chemical structure of molecules, resulting from the chlorophylline photosynthesis, carried out by autotrophies organisms. Lots of biomass from agricultural, agri-food and forestry sectors can be used for energy purposes, representing an essential renewable energy source that, if appropriately managed, can help to reduce the negative environmental impacts arising from the exploitation of fossil fuels. The possibility of using biomass for a speciﬁc production process mainly depends on its physical and chemical properties. This paper is organized in two sections: in the ﬁrst one, the most important biomass used worldwide for energy generation (thermal energy and/or electric energy), as well as its properties, are described. In the second one, the main biomass-to-energy processes (thermochemical and biochemical conversions) are shortly explained. Finally, some emerging techniques (such as bio-methane and bio-hydrogen production) are discussed in more detail.